2015
DOI: 10.1016/j.jclinepi.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Discordances originated by multiple meta-analyses on interventions for myocardial infarction: a systematic review

Abstract: To clarify the impact of multiple (covering the same population,intervention, control, and outcomes) systematic reviews (SRs) on interventions for myocardial infarction (MI). STUDY DESIGN AND SETTING: Clinical Evidence (BMJ Group) sections and related search strategies regarding MI were used to identify multiple SRs published between 1997 and 2007. Multiple SRs were classified as discordant if they featured conflicting results or interpretation of them.RESULTS: Thirty-six SRs (23.5% of 153 on the treatment or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…Since the time the searches were conducted for the current study, Cochrane authors have updated an earlier review of anti-VEGF effectiveness and also have published a review comparing the systemic safety of ranibizumab versus bevacizumab. 102,103 Unlike other research that has found duplication of systematic reviews on the same topic to be wasteful 101,104 or lead to discordant findings, 105,106 we conclude that sequential systematic reviews that at first glance appear to cover similar topics instead may represent evolution in the research question with increased clinical experience and serve as an indication of a rapidly developing field.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Since the time the searches were conducted for the current study, Cochrane authors have updated an earlier review of anti-VEGF effectiveness and also have published a review comparing the systemic safety of ranibizumab versus bevacizumab. 102,103 Unlike other research that has found duplication of systematic reviews on the same topic to be wasteful 101,104 or lead to discordant findings, 105,106 we conclude that sequential systematic reviews that at first glance appear to cover similar topics instead may represent evolution in the research question with increased clinical experience and serve as an indication of a rapidly developing field.…”
Section: Discussioncontrasting
confidence: 55%
“…Some reasons for differing conclusions are understandable, for example when the studies synthesized in systematic reviews were conducted at dissimilar time periods or included different types of study designs. 8 But sometimes differing conclusions can be ascribed to use of systematic review methods that are potentially subject to bias. 9 …”
Section: Introductionmentioning
confidence: 99%
“…We would hope that overviews on the same topic would nd the same results and come to similar conclusions, but this is often not the case with systematic reviews [12,[35][36][37]. Potential discrepancies can cause endless debates (e.g.…”
Section: Potential For Discrepant Results and Conclusion Across Overlapping Overviewsmentioning
confidence: 99%
“…Overviews may alternatively aim to answer narrow, focused clinical questions, and to identify and explore reasons for variation in the results, interpretation, or conclusions of systematic reviews analysis [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The summary odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to indicate the association of the different HLA-DRB1 alleles with the development of different ACPA-status RA. The statistical heterogeneity among the studies was assessed by a chi-square-based Q statistic test and the I 2 statistic (I 2 = 0% -50%, no or moderate heterogeneity; I 2 > 50%, significant heterogeneity) [15] [16]. If the homogeneity was significant (P > 0.10 for the Q test or I2% > 50%), the random-effect model was used.…”
Section: Discussionmentioning
confidence: 99%